2017
DOI: 10.1007/s10899-017-9690-6
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Beliefs in Luck are Linked to Gambling Problems via Strengthened Cognitive Biases: A Mediation Test

Abstract: Problematic patterns of gambling and their harms are known to have culturally specific expressions. For ethnic Chinese people, patterns of superstitious belief in this community appear to be linked to the elevated rates of gambling-related harms; however, little is known about the mediating psychological mechanisms. To address this issue, we surveyed 333 Chinese gamblers residing internationally and used a mediation analysis to explore how gambling-related cognitive biases, gambling frequency and variety of ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, this may also mean that, in their superstitious behavior, the Chinese may be more motivated by protective functions of superstitions, driven by hope and anticipated regret, as opposed the fear of a negative event (Vaidyanathan et al, 2018). Lim and Rogers (2017) further note that the Chinese tend to believe in luck as an internal and stable property of a person, while external sources of luck, to which (un)lucky hotel floor and room number would belong, are open to manipulations through culturally and sanctioned practices. Thus, not bothered by and not seeking a change of an unlucky floor and room assignment in hotels might be viewed as non-conformance to socially accepted practices of ensuring one's luck, supporting the idea of socialadjustive function of superstitious behavior (Vaidyanathan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this may also mean that, in their superstitious behavior, the Chinese may be more motivated by protective functions of superstitions, driven by hope and anticipated regret, as opposed the fear of a negative event (Vaidyanathan et al, 2018). Lim and Rogers (2017) further note that the Chinese tend to believe in luck as an internal and stable property of a person, while external sources of luck, to which (un)lucky hotel floor and room number would belong, are open to manipulations through culturally and sanctioned practices. Thus, not bothered by and not seeking a change of an unlucky floor and room assignment in hotels might be viewed as non-conformance to socially accepted practices of ensuring one's luck, supporting the idea of socialadjustive function of superstitious behavior (Vaidyanathan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For the Asian cohort, the paranormal scale is based on Huang and Teng's (2009) Chinese superstitious belief scale. This scale has also been tried and tested in different Chinese contexts (Kim et al, 2016;Lim and Rogers, 2017). The Chinese superstitious belief scale contains six underlying dimensions: Homonyms; Traditional customs; Power of crystal; Horoscope; Feng-shui; and Luck for gambling.…”
Section: Research Instrumentmentioning
confidence: 99%
“…Others report seeing ghosts (Pew Research Center, 2009) or receiving messages from deceased loved ones (Exline, in press; Streit-Horn, 2011). Many also attribute events to the impersonal forces of fate/destiny (Au & Savani, 2019; Flórez et al, 2009; Green et al, 2004; Norenzayan & Lee, 2010), karma (White & Norenzayan, 2019; Willard et al, 2020), and luck (Lim & Rogers, 2017; Stauner et al, 2017; Woolley & Kelley, 2020).…”
Section: Supernatural Attributionsmentioning
confidence: 99%
“…Although perceived ghost encounters usually bring fear (Hinton et al, 2020), believing that a deceased loved one is sending messages may provide great comfort (Exline, in press; Streit-Horn, 2011). And in terms of impersonal forces, fate beliefs have been linked with avoidance of medical exams (Green et al, 2004), karma beliefs with prosocial choices (White & Norenzayan, 2019), and luck beliefs with gambling behaviors (Lim & Rogers, 2017).…”
Section: Supernatural Attributionsmentioning
confidence: 99%
“…Prior studies have suggested that many Chinese believe that one's success and wealth depend on fate, luck, Feng Shui or an accumulation of good deeds (Prentice & Wong, 2015). However, Chinese gamblers are less likely to seek professional help than other cultural groups despite having financial problems (Lim & Rogers, 2017). Recent researchers of residents' attitudes toward the gaming industry have observed that the Chinese exhibit mixed emotions toward the industry (Kang, et al, 2008;Luo & Xiao, 2017).…”
Section: Leisure Gaming In the Communitymentioning
confidence: 99%